Delayed Interval Delivery of the Second Twin: A Case Report - Tan, Orkun; Hızlı, Deniz; Kataş, Bekir; Al, Atakan; Dölen, İsmail (Gynecology Obstetrics & Reproductive Medicine, 2006)
A 27 y ear old women at 23+1 weeks twin gestation deliv ered the f irst f etus. The umblical cord was ligated and the placenta was left in situ. No cerclage was applied. She was administered intravenous antibiotics and ritodrine. The second twin was deliv ered after 23 days of the delivery of the f irst f etus. Bedrest, prophy lactic antibiotics with or without cerclage and non-aggressive tocolysis is reasonable f or delay ing the deliv ery of the second twin with chorioamnionitis.